MGIMO Educational Standards: Goal and Contents of Professional Language Training of IR Economics Students - A. A. Kizima (Vestnik MGIMO-Universiteta)
The article gives a methodological analysis of MGIMO-University own education standards and programmes. The relevance of the article is explained by the necessity to define the goals and contents of professional language training of IR economics students at MGIMO-University after a transfer to own education standards. The researcher used competence-based and cultural studies approaches with reference to the didactic principles of accessibility, systematic, consistency, necessity and sufficiency. The author used a set of methods including the method of theoretical analysis, the method of synthesis and systematization, summative method. The article addresses the difference in the training of IR economists and economists in other spheres of economics, underlines the importance of professional language training of IR economics students, analyses the specifics of professional language training of IR economists from the standpoint of competence-based approach by comparing the competences presented in the Federal State Education Standards of Higher Education and MGIMO own education standards. The author gives a definition of goal and contents of professional language training of IR economics students as well as didactic principles of contents choice that define the effectiveness of training. In conclusion the author points out that the contents of professional language training of IR economics students based on MGIMO own education standards are approached as the system of professional knowledge, skills and competence leading to successful intercultural communication.